Исследование воспалительных маркёров на преклинической стадии болезни Гентингтона - Androsova, L. V.; Ponomareva, N. V.; Simonov, A. N.; Klyushnikov, S. A.; Otman, I. N.; Klyushnik, T. P. (Патогенез, 2022)
Тезисы конференции